Pre and post-welding annealing influence on the microstructure of a 7475-T7351 aluminum alloy joining by friction stir welding / Influência do recozimento pré e pós-soldagem na microestrutura de uma liga de alumínio 7475-T7351 que se une por fricção - de Souza, Carolina Alencar Caldeira (2022)
Friction Stir Welding (FSW) promotes the joining of sheets due to localized plastic deformation and heating by displacing a non-consumable tool. This work aimed to verify the influence of an annealing heat treatment performed at 300 and 500 ºC with 15 minutes of soaking times, before and after the FSW of a 7475-T7351 aluminum alloy. The macrographs of the welded joint (top and cross section) and micrographs of the cross section was obtained by a stereoscope and optical microscope were analyzed and the mechanical behavior was characterized by uniaxial tensile tests. It was concluded that the annealing heat treatments did not influence significantly the nugget grain size, but there are indications that the realization of these before the FSW, provide a homogeneity in the mechanical properties of the welded joint and the base material.